Active frequency support capability evaluation of photovoltaic stations based on bi-level evaluation method - Zhengxi Li; Libin Yang; Wanpeng Zhou; Chunlai Li (Scientific Reports)
Abstract With the increasing penetration of photovoltaic (PV) in power grid, to cope with the deteriorating frequency security of the system, PV stations are required to participate in frequency regulation by grid codes. Knowing the active frequency support capability (AFSC) of PV stations is essential for strategy design of frequency response. Therefore, a comprehensive indicator system and an integrated evaluation method are proposed to evaluate the AFSC of PV stations. By considering several national standards, a comprehensive evaluation indicator system of AFSC for PV stations is established from three aspects: frequency stability, power support, and power regulation. In order to avoid the impact of subjective factors, this paper proposes a bi-level evaluation model combining decision-making trial and evaluation laboratory (DEMATEL), technique for order preference by similarity to ideal solution (TOPSIS), and antagonistic interpretive structural modeling (AISM) for weighting the indicators. Finally, case study was performed based on IEEE 39-bus test system integrated with PV station. The results show that the proposed indicator system and evaluation method can reflect the AFSC of PV stations effectively. The evaluation indicator system for the AFSC of PV stations is also developed into software to promote its application and implementation.